2014
DOI: 10.1007/s00431-014-2444-x
|View full text |Cite
|
Sign up to set email alerts
|

Examining a possible association between human papilloma virus (HPV) vaccination and migraine: results of a cohort study in the Netherlands

Abstract: Since the introduction of the bivalent human papilloma virus (HPV) vaccine in the Netherlands, migraine has been reported as a notable event in the passive safety surveillance system. Research on the association between HPV vaccination and migraine is needed. Therefore, potential migraine cases in 2008–2010 were selected from a group of general practitioners and linked to the vaccination registry. Data were analysed in three ways: (i) incidences of migraine postvaccination (2009/2010) were compared to pre-vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…A cohort study conducted in the Netherlands identified no significant increase in the risk of migraine after immunisation with the bivalent HPV vaccine. 40 Although the study was limited by insufficient sample size and lack of power, this result was consistent with strength and limitations of this study By linking two different nationwide databases-a vaccine registry and health insurance database-our study provided results for the entire population of South Korea. 41 Using this nationwide linked database allowed us to detect associations between HPV vaccine and rare or serious diseases without losing statistical power.…”
Section: Discussionsupporting
confidence: 83%
“…A cohort study conducted in the Netherlands identified no significant increase in the risk of migraine after immunisation with the bivalent HPV vaccine. 40 Although the study was limited by insufficient sample size and lack of power, this result was consistent with strength and limitations of this study By linking two different nationwide databases-a vaccine registry and health insurance database-our study provided results for the entire population of South Korea. 41 Using this nationwide linked database allowed us to detect associations between HPV vaccine and rare or serious diseases without losing statistical power.…”
Section: Discussionsupporting
confidence: 83%
“…The safety of the vaccines has continued to be monitored through population‐based vaccine safety surveillance systems, studies and follow up of trial participants . The WHO Global Advisory Committee for Vaccine Safety continues to regularly review these data and confirm safety .…”
Section: Current Knowledge About the Efficacy And Safety Of Prophylacmentioning
confidence: 99%
“…The safety of the vaccines has continued to be monitored through population-based vaccine safety surveillance systems, studies and follow up of trial participants. [10][11][12][13][14][15][16][17][18] The WHO Global Advisory Committee for Vaccine Safety continues to regularly review these data and confirm safety. 19 Failure to achieve high population coverage limits the full potential benefits gained from vaccination, which are observed in countries with successfully implemented vaccine programs.…”
Section: Current Knowledge About the Efficacy And Safety Of Prophylacmentioning
confidence: 99%